1992
DOI: 10.1007/bf00232695
|View full text |Cite
|
Sign up to set email alerts
|

Induction of rosmarinic acid biosynthesis in Lithospermum erythrorhizon cell suspension cultures by yeast extract

Abstract: A transient increase in rosmarinic acid (RA) content in cultured cells of Lithospermum erythrorhizon was observed after addition of yeast extract (YE) to the suspension cultures, reaching a maximum at 24 hr. The highest increase of the RA content (2.5-fold) was obtained when 6-day-old cells in the exponential growth phase were treated with YE. Preceding the induced RA accumulation, phenylalanine ammonia-lyase (PAL) activity increased rapidly, whereas tyrosine aminotransferase (TAT) activity was largely unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 17 publications
6
32
1
2
Order By: Relevance
“…Intact L. erythrorhizon plants produce caffeic acid derivatives, such as rosmarinic acid (Figure 3), and cultured L. erythrorhizon cells were shown to produce this caffeic acid dimer (Mizukami et al 1992(Mizukami et al , 1993. Moreover, transfer of L. erythrorhizon cells from LS medium to M9 medium resulted in an increase in production of lithospermic acid B, a caffeic acid tetramer, comparable to the level of shikonin derivatives (Yamamoto et al 2000b).…”
Section: Other Metabolites Highly Accumulated In L Erythrorhizon Cellsmentioning
confidence: 99%
“…Intact L. erythrorhizon plants produce caffeic acid derivatives, such as rosmarinic acid (Figure 3), and cultured L. erythrorhizon cells were shown to produce this caffeic acid dimer (Mizukami et al 1992(Mizukami et al , 1993. Moreover, transfer of L. erythrorhizon cells from LS medium to M9 medium resulted in an increase in production of lithospermic acid B, a caffeic acid tetramer, comparable to the level of shikonin derivatives (Yamamoto et al 2000b).…”
Section: Other Metabolites Highly Accumulated In L Erythrorhizon Cellsmentioning
confidence: 99%
“…RA production in cultured plant cells was earlier shown to be enhanced by addition of elicitors such as yeast extract (YE) and methyl jasmonate (MJ), as exemplified in Lithospermum erythrorhizon cell cultures (Mizukami et al 1992 and1993). Elicitation by YE or MJ up-regulated the activities of both phenylalanine ammonia-lyase (PAL) and 4-hydroxyphenylpyruvate reductase (HPR), entrypoint enzymes for the phenylpropanoid pathway and tyrosine-derived pathway, respectively.…”
mentioning
confidence: 99%
“…The combined ethyl acetate extract was evaporated, and the residue was dissolved in 25 ml methanol containing 0.1% (v/v) acetic acid. The amount of RA formed by the enzymatic reaction was determined by HPLC according to the previously described method (Mizukami et al 1992).…”
mentioning
confidence: 99%
“…Detailed studies had already confirmed formation of PPA beside shikonin and some of its derivatives in the root cell culture of L. erythrorhizon (Mizukami et al, 1992(Mizukami et al, , 1993. There are two precursors for shikalkin formation, geranylpyrophosphate (GPP) and p-hydroxybenzoic acid (PHBA).…”
Section: Resultsmentioning
confidence: 99%
“…Fruitful in vitro cell culture of the L. erythrorhizon root provided the plant scientists with a suitable model to study phenolic secondary metabolites pathways in detail. Results of such studies have disclosed that the L. erythrorhizon callus is also able to produce polyphenolic acids (PPA) like rosmarinic acid (RA) (Mizukami et al, 1992) and lithospermic acid (Yamamoto et al, 2000) not observed in the root of this species naturally. Besides, it has been shown that the yield of PPA production by the L. erythrorhizon cell culture can be enhanced, if the production of shikalkin derivatives is inhibited by light (Gaisser & Heide, 1996).…”
Section: Introductionmentioning
confidence: 99%